KAJIAN NILAI-NILAI EDUKATIF DALAM BUDAYA JAWA SEBAGAI BENTUK INVENTARISASI DAN TRANSFORMASINYA BAGI PENGUATAN KARAKTER (STUDI KASUS DI LINGKUNGAN KELUARGA PRIYAYI DI SURAKARTA) - Kurniawan, Dadan Adi (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2013)
From this research it can be concluded: (1) educational values identified in Javanese culture to 28 values. Those values, among others, religious, respect, harmony, mutual assistance, harmony, caring, humble, appreciative, loyal, honest, fair, sincere, creative, hard work, discipline, teamwork, responsibility, perseverance, self- , brave, strong, self-sacrificing, consistent, vigilant, steadfast and patient, clever grateful, democratic, united in love and unity. (2) Transformation of the Javanese cultural values in in the aristocratic family in Surakarta classified into two kinds. The first is the family of aristocratic who lived around the palace belonging transformation progress is change or shift in cultural values towards progress. The second, aristocratic family who live far away from the palace also considered underwent a transformation progress but the rate of transformation regress (toward decline) higher than the aristocratic families who live around the palace, (3) educational values in Javanese culture is relevant to 16 character value proposed by Raharjo and 18 character value issued by the Ministry of National Education of Indonesia in 2010. Keywords: educational value, Javanese culture, transformation, character value, character education.